Performance Analysis of Capillary-Compensated Hydrostatic Lead Screws with Discontinuous Helical Recesses Including Influence of Pitch Errors in Nut. Issue 6 (2nd November 2017) - Zhang, Yongtao; Chen, Shujiang; Lu, Changhou; Liu, Zichao
ABSTRACT: This article investigates the axial static and dynamic characteristics of capillary-compensated hydrostatic lead screws with discontinuous helical recesses considering the influence of the pitch errors of the nut. The mathematical model is based on the Reynolds equation, including rotational lubricant inertia and the flow continuity equation. The finite difference method and the perturbation technique are applied. The results show that the pitch errors cause the inequality of recess pressures on the same flank surface of the nut thread; the influence of pitch errors on the axial load capacity is not significant within the dimensionless axial displacement of the nut of 0.6, but the effect on the axial stiffness and damping coefficients is significant under larger axial displacement.